Sharia Based Approaches to Global Digital Governance: Ethical Implications of Blockchain and Cryptocurrency in Muslim Communities - Laras Annisa Ulfitri Nedi; Chetrine Alya Rinaima (International Forum of Researchers and Lecturers, 2024)
The integration of blockchain technology and cryptocurrency within the framework of Islamic finance has raised significant ethical, legal, and regulatory concerns. Blockchain technology, known for its transparency, decentralization, and immutability, offers a promising solution for enhancing financial inclusion, transparency, and security in financial transactions. However, the use of cryptocurrencies, such as Bitcoin and Ethereum, introduces complexities due to their speculative nature, which may violate Sharia principles like gharar (excessive uncertainty) and riba (usury). This study explores the compatibility of blockchain and cryptocurrency with Sharia law, focusing on the challenges and opportunities that arise in the context of Islamic finance. The study analyzes existing fatwas (Islamic legal opinions), regulatory frameworks, and the application of Sharia principles to emerging financial technologies. It discusses the ethical dimensions of blockchain and cryptocurrency, such as their potential to promote fairness and transparency, while addressing concerns about privacy violations and the risks associated with unregulated trading. Furthermore, the research highlights the lack of standardized global regulations for cryptocurrency and blockchain, which complicates their adoption in Muslim-majority countries. The study also emphasizes the importance of establishing Sharia-compliant governance frameworks and regulatory standards to ensure the ethical use of these technologies. Finally, the study provides recommendations for further research in the intersection of Islamic law, digital finance, and global governance frameworks, focusing on the development of policies that ensure Sharia-compliant digital assets and technologies.